2005
DOI: 10.1080/00420980500060186
|View full text |Cite
|
Sign up to set email alerts
|

Paying for Quietness: The Impact of Noise on Geneva Rents

Abstract: Using the hedonic approach, this paper analyses housing market data to infer the impact of noise on rents in Geneva, Switzerland. Using three different databases, including a geographical information system (GIS), structural, accessibility and environmental variables were obtained for a large proportion of apartments rented in Geneva. The paper is thus in line with the new generation hedonic models, which exploit the vast potential of GIS to obtain large databases including detailed characteristics of the apar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 15 publications
4
53
0
3
Order By: Relevance
“…HPM has been applied to very different urban contexts: in cities such as Geneva [7][8][9] or Glasgow [10]; metropolises such as Naples [11,12], Tokyo [13], Chicago, Denver, Philadelphia, Baltimore, Washington DC [14,15], or Seoul [16]; and in informal settlements in Asian cities such as Bangkok and Jakarta [17]. Studies have either focused on one specific local context [18,19], or compared various local environments ranging over wide territorial areas to estimate the effect of the proximity to natural attractions [20][21][22], or big infrastructures such as airports [23].…”
Section: The Use Of Hedonic Approach For the Assessment Or Urban Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…HPM has been applied to very different urban contexts: in cities such as Geneva [7][8][9] or Glasgow [10]; metropolises such as Naples [11,12], Tokyo [13], Chicago, Denver, Philadelphia, Baltimore, Washington DC [14,15], or Seoul [16]; and in informal settlements in Asian cities such as Bangkok and Jakarta [17]. Studies have either focused on one specific local context [18,19], or compared various local environments ranging over wide territorial areas to estimate the effect of the proximity to natural attractions [20][21][22], or big infrastructures such as airports [23].…”
Section: The Use Of Hedonic Approach For the Assessment Or Urban Qualitymentioning
confidence: 99%
“…The environmental characteristics that are more often evaluated and are believed to have a considerable impact on urban quality and on real estate values are related to air pollution [9,14,16,26] or noise impact [7,11,23], further to the already cited example of urban parks and green spaces [5]. Among the positive aspects evaluated, we found a perspective that had a relevant influence on housing values, in particular, views on urbanized, agricultural, or wooded areas [27], lakes [20], on open spaces offering recreational attractions, and slowing down further urbanization [28].…”
Section: The Use Of Hedonic Approach For the Assessment Or Urban Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nor are these effects restricted to physiological impacts. Baranzini and Ramirez (2005) have reported that the overall economic impact of urban noise on private rents in Geneva is 0.7 per cent per decibel and 1 per cent when airplace noise exclusively was modelled. These effects were more pronounced in neighbourhoods where the prevailing background noise level was low, in other words when sounds 'like airplanes' were seen to be 'out of place'.…”
Section: Ecology Of Soundmentioning
confidence: 99%
“…Bourassa, Hoesli, and Sun (2004) Frew and Wilson (2002) estimate the connection between location and property value. Baranzini and Ramirez (2005) ask what tenants must pay for quietness in their study of what impact noise has on Geneva rents. The reader notices that these studies employ attributes with the physical units or properties of the physical surroundings when they explain variation in price and rent.…”
Section: Introductionmentioning
confidence: 99%